1995
DOI: 10.1037/0022-006x.63.6.928
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement desensitization and reprocessing (EMDR) treatment for psychologically traumatized individuals.

Abstract: The effects of 3 90-min eye movement desensitization and reprocessing (EMDR) treatment sessions on traumatic memories of 80 participants were studied. Participants were randomly assigned to treatment or delayed-treatment conditions and to 1 of 5 licensed therapists trained in EMDR. Participants receiving EMDR showed decreases in presenting complaints and in anxiety and increases in positive cognition. Participants in the delayed-treatment condition showed no improvement on any of these measures across the 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
198
1
9

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(221 citation statements)
references
References 27 publications
13
198
1
9
Order By: Relevance
“…Findings revealed that the majority of studies reported only partial information; of 34 studies reviewed, less than half (n = 11) reported pretreatment exclusion and attrition data, and only two studies (Tarrier et al, 1999;Wilson, Becker, & Tinker, 1995) provided initial screening data. Surprisingly, three studies neglected to report the number of participants randomized into treatment, citing only the final number of study completers and preventing complete estimation of treatment dropout rates.…”
Section: Reporting Of Study Enrollment Datamentioning
confidence: 99%
“…Findings revealed that the majority of studies reported only partial information; of 34 studies reviewed, less than half (n = 11) reported pretreatment exclusion and attrition data, and only two studies (Tarrier et al, 1999;Wilson, Becker, & Tinker, 1995) provided initial screening data. Surprisingly, three studies neglected to report the number of participants randomized into treatment, citing only the final number of study completers and preventing complete estimation of treatment dropout rates.…”
Section: Reporting Of Study Enrollment Datamentioning
confidence: 99%
“…One of the consistent findings of research on psychological treatments for trauma, in general, is the effectiveness of exposure-based techniques for obvious PTSD symptoms (e.g., Foa, Rothbaum, Riggs, & Murdock, 1991;Wilson, Becker, & Tinker, 1995). However, Wilson et al note that, in treatments targeting specific PTSD symptoms, evidence for improvements in more general measures of psychological functioning has been lacking.…”
mentioning
confidence: 96%
“…The final exclusion criteria were scores below 0.60 (T = 40) on the Global Severity Index (GSI) of the Symptom Checklist-90-Revised (SCL; Derogatis, 1983) or below 15 on the Impact of Event Scale (IES; Horowitz, 1986). These cutoffs are based on outpatient norms on these measures (Derogatis, 1983;Wilson et al, 1995). In order of prevalence, most clients were excluded because of participation in another psychosocial or pharmacological treatment, severity of current problems with substance abuse, violent relationships, or self-harm behavior, and scores below cutoffs on the above measures.…”
Section: Participantsmentioning
confidence: 99%
“…His depression, which should have been another inhibiting factor, did not appear to interfere with the effectiveness of EMDR. Though EMDR does not always result in such rapid resolution of trauma, the behaviors observed in this case are commonly observed by therapists using EMDR (Greenwald, 1999;McCann, 1992;Shapiro, 1989aShapiro, , 1995Thomas & Gafner, 1993;Tinker & Wilson, 1999;Wolpe & Abrams, 1991) while the comparatively rapid elimination of PTSD symptomatology (e.g., within three sessions) has been documented in repeated controlled studies (e.g., Ironson et al, 2002;Rothbaum, 1997;S.A. Wilson et al, 1995).…”
Section: Case Examplementioning
confidence: 99%